1999
DOI: 10.1016/s0378-1097(99)00402-4
|View full text |Cite
|
Sign up to set email alerts
|

Inability of encapsulated Klebsiella pneumoniae to assemble functional type 1 fimbriae on their surface

Abstract: We screened phase variants of Klebsiella pneumoniae isolates for the expression of capsule and type 1 fimbriae and found that all of the 22 blood isolates were encapsulated and did not express type 1 fimbriae while 10 of 11 urinary tract isolates expressed type 1 fimbriae but were unencapsulated. Phase variants from selected isolates were found to be either unencapsulated and fimbriated or lacked both structures. Variants expressing both structures were not detected. Fimbrial subunits FimH and FimA were locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The unencapsulated derivatives of strain K21a and the K50 strain were obtained as described elsewhere (38,55). A spontaneous unencapsulated mutant, 50-30F, from the parent K50 strain was obtained by selecting nonmucoid colonies as described previously (38). For these experiments, bacteria were grown on Trypticase soy agar (Difco) for 24 h at 37°C and harvested by scraping the confluent growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unencapsulated derivatives of strain K21a and the K50 strain were obtained as described elsewhere (38,55). A spontaneous unencapsulated mutant, 50-30F, from the parent K50 strain was obtained by selecting nonmucoid colonies as described previously (38). For these experiments, bacteria were grown on Trypticase soy agar (Difco) for 24 h at 37°C and harvested by scraping the confluent growth.…”
Section: Methodsmentioning
confidence: 99%
“…Although the phenomenon of phase variation in capsular expression has been long appreciated for E. coli and many other bacterial organisms (45), it has been only recently documented for K. pneumoniae (38). Phase variation represents an apparently random, bidirectional, on-off control of bacterial genes that can take place at relatively high frequency, i.e., approximately 10,000 times more frequently than classical mutational events (44).…”
mentioning
confidence: 99%
“…The virulence of CPS may derive from enhanced colonization in the airway spaces and reduced adhesion to host cells by transcriptional regulation (23). Previously, isogenic capsule-negative strains (DCPS) showed higher adhesion to airway cells (24).…”
Section: Raft-dependent Bacterial Internalization Is Enhanced By Delementioning
confidence: 99%
“…Colonization of the upper respiratory tract by gram-negative bacteria precedes entry of the organisms into the lung. Because capsules can interfere with the expression or function of adhesins required for the colonization of epithelial cells by the organisms, it is likely that most of the bacteria colonizing the upper respiratory tract or other epithelial surfaces are in the noncapsulated phase (19,57,81,83). Lung collectin SP-D, which reacts with a conserved region of the LPS core, may provide early protection against all strains of noncapsulated phenotypes either by opsonizing the bacteria to enhance their phagocytosis or by agglutinating the bacteria, which may inhibit their adhesion to the upper respiratory epithelium (71,79).…”
Section: Integrative Model For Klebsiellamentioning
confidence: 99%
“…Polymannose-containing O serotypes can bind to SP-D, while those that lack such structures cannot. In vitro studies have shown that Klebsiella can undergo phase variation between capsulated and noncapsulated phenotypes (57). As a result, capsulated bacteria that emerge during the infection are prone to escape SP-D recognition.…”
Section: Integrative Model For Klebsiellamentioning
confidence: 99%